Effects of site preparation and reindeer grazing on the early-stage success of Scots pine regeneration from seeds in northern Finland and Sweden - Miettinen, Janne; Hallikainen, Ville; Hypponen, Mikko; Bergsten, Urban; Winsa, Hans; Valikangas, Pekka; Hiltunen, Arto; Aatsinki, Pasi; Rautio, Pasi (2022)
The importance of sufficient soil scarification to ensure the regeneration of Scots pine on sub-dry and more fertile sites has been emphasized in many studies. Here we aimed to study, how site preparation intensity affects the early success of natural regeneration and sowing (bare seeds and seed pellets) of Scots pine with or without the reindeer grazing. The study area was located in northern Finland and Sweden where five site preparation methods were compared: unprepared control, logging machine tracks, Huminmix (mixing the mineral soil and organic layer), disc trenching and intensive disc trenching. In each of these we used direct seeding, seed pellets and natural regeneration. Results revealed that even the lightest site preparation methods can provide sufficient regeneration results while the reindeer grazing limits the optimal regeneration result. Huminmix and even the track of the logging machine could provide satisfactory regeneration results both in direct seeding and natural regeneration. This could facilitate the coexistence of forest management, reindeer herding and other land use forms in the same stands and area. The use of seed pellets needs further research, but it may have potential due to lower consumption of seeds and less need for site preparation.